Sistem Informasi Antropometri Terintegrasi Dengan Sistem Tertanam Sebagai Pengukur Berat Dan Tinggi Balita - Nugroho Budi Wicaksono; Rinta Kridalukmana; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
Indonesian children’s growth are monitored monthly and can be seen by the KMS graphic and posyandu cadre’s book. The data from posyandu activity will be evaluated by the government health department. In practice, there are many obstacles to make posyandu works ideally. First, the cadres of posyandu have a difficulty to use the conventional anthropometric equipment, so the measurement data may not be valid and precise. Second, noting the KMS graphic needs an accuracy. Third, the measurement result in posyandu is not rapidly integrated to the central health data. A technology innovation of automatization anthropometry measurement called OTOTIM designed for infants that supported by an integrated information system is needed to solve those problems. OTOTIM designed to make anthropometric measurement for infants more fast, valid, and accurate. The measurement result will be stored in the database and transferred to an image that describe the nutrition status in the KMS. Microcontroller will process the data from load sensor that measure baby’s weight and ping sensor that measure baby’s height. Then those raw data will be sent to main component of OTOTIM, which is the software itself to gain informative result of measurement, that consist of right suggestion on what kind of treatment used to take care various nutrition condition of infant and comparison against the previous measurement. OTOTIM will also generate statistics which group the infant by nutritional condition for each month. Those statistics will also include information on how percentage of male and female babies which have certain nutritional condition. However those statistic will provide information which is relevant only for specific district as OTOTIM used in regional manner. In order to create statistic which is relevant to consumed by public, those measurement data must be processed in central server which can calculate whole data and grouped them by nutritional condition. OTOTIM introduces the central server that bring synchronization service between OTOTIM software which is installed locally on client PC and the server itself. OTOTIM software have to establish a connection to server to publish subdistrict-specific statistic, however this connection is not mandatory to run primary function. So if client have trouble to connect, this will not interrupt the primary function as OTOTIM supposed to run in less-signal environment.